Environmental protection and conservation the case of Laguna Lake and other theoretical approaches - Santos, Antonio L. (2010)
The environment provided the matrix upon which man's survival depends. One way of better understanding the environment is to take a closer look at the interplay of various stakeholders in a given situation or problem, like water pollution.

This paper looks into the theoretical and empirical findings on water pollution in Laguna Lake utilizing the "interfaces" among the major stakeholders in the lake as an empirical data-base with the aim in view of co-managing it for environmental conservation and protection.